Neoliberalism in Websites of Schools of Education and Teacher Education Programs: Comparison between Canadian and American Public Universities (Alberta Journal of Educational Research, 2019)
This study analyzes websites of university-based Schools of Education and Teacher Education Programs, and points to the (intentional or unintentional) active role these institutions play in maintaining and supporting neoliberal ideology. The study uses a qualitative method to examine websites of 30 public universities, 15 American and 15 Canadian. Using a grounded theory approach, five neoliberal-related features are identified: marketing, business terminology, employability, economic orientation, and outcome-based approach. The latter two features were found only in the American websites. The paper discusses implications for each of the features, as well as for the differences between American and Canadian institutions. Teacher educators are encouraged to take the findings seriously as there is a concern that neoliberal trends and practices will continue to seep more deeply into Teacher Education Programs.Cette étude analyse les sites Web de programmes universitaires de formation des enseignants et fait ressortir le rôle actif (intentionnel ou non) que jouent ces institutions dans le maintien et l’appui du néolibéralisme. L’étude emploie une méthode qualitative pour examiner les sites Web de 30 universités publiques, dont 15 américaines et 15 canadiennes. Une approche théorique à base empirique a permis d’identifier cinq éléments liés au néolibéralisme : le marketing, le vocabulaire commercial, l’employabilité, l’orientation économique et une approche axée sur les résultats. Les deux derniers éléments étaient présents seulement dans les sites Web américains. L’article discute des retombées de chacun des éléments et évoque les différences entre les institutions américaines et canadiennes. On encourage les formateurs d’enseignants de prendre ces résultats au sérieux car on craint que les tendances et les pratiques néolibérales continueront à s’infiltrer de plus en plus dans les programmes de formation des enseignants. Mots clés: établissements de formation, programmes de formation des enseignants, sites Web, marketing